2017
DOI: 10.3390/atmos8110216
|View full text |Cite
|
Sign up to set email alerts
|

The Air-Sea Nitrous Oxide Flux along Cruise Tracks to the Arctic Ocean and Southern Ocean

Abstract: Nitrous oxide is a trace gas with two global environmental effects: it depletes stratospheric ozone and contributes to the greenhouse effect. Oceans are one of the most significant nitrous oxide sources; however, there are ocean areas whose contributions to the nitrous oxide budget are not yet well studied. The Southern Ocean and the Arctic Ocean feature strong winds and portions that are covered by sea ice. These intense environmental conditions and the remoteness of these regions hamper fieldwork; hence, ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…Sea-air fluxes of CH4 and N2O integrated over the mixed layer residence time of each gas were calculated, incorporating variability in wind speed, sea ice cover, and sea level atmospheric pressure. This approach contrasts with some previous studies based on Arctic Ocean seawater measurements that have calculated sea-air fluxes of CH4 and N2O using either instantaneous wind speeds (Heo et al, 2021;Hirota et al, 2009;Zhan et al, 2017), or wind speeds averaged over a fixed amount of time, e.g., one month (Li et al, 2017;Lorenson et al, 2016). As gas exchange is a nonlinear function of wind speed, high wind speeds have a disproportionately large impact on the total sea-air flux.…”
Section: Sea-air Flux Calculationsmentioning
confidence: 88%
“…Sea-air fluxes of CH4 and N2O integrated over the mixed layer residence time of each gas were calculated, incorporating variability in wind speed, sea ice cover, and sea level atmospheric pressure. This approach contrasts with some previous studies based on Arctic Ocean seawater measurements that have calculated sea-air fluxes of CH4 and N2O using either instantaneous wind speeds (Heo et al, 2021;Hirota et al, 2009;Zhan et al, 2017), or wind speeds averaged over a fixed amount of time, e.g., one month (Li et al, 2017;Lorenson et al, 2016). As gas exchange is a nonlinear function of wind speed, high wind speeds have a disproportionately large impact on the total sea-air flux.…”
Section: Sea-air Flux Calculationsmentioning
confidence: 88%
“…The Atlantic Meridional Transect 7 is an example of an annually repeated cruise on which N 2 O measurements have been made over two decades (Forster et al, 2009;Rhee et al, 2009;Grefe and Kaiser, 2014). N 2 O has been repeatedly measured during the annual Chinese Arctic and Antarctic Expeditions (CHINARE) to the Arctic and Southern Oceans, see e.g., (Zhan and Chen, 2009;Zhan et al, 2015Zhan et al, , 2017. Beside these examples, there are few published time-series measurements of open ocean water column N 2 O distributions from repeat hydrographic sections (Nevison et al, 1995;Fenwick and Tortell, 2018).…”
Section: Repeat Hydrographic Lines and Time-series Stationsmentioning
confidence: 99%
“…The distribution of SC N 2 O exhibited different patterns from the distribution of NC N 2 O within the surface layer. These results are indicators of the effect of the physical solubility, which is mainly determined by T and S 34 , and is dominant in the NC (cold and fresh) compared to the SC (warm and saline) 23 . In addition to the physical solubility, Randall et al 64 reported that the N 2 O of sea-ice meltwater was greatly under-saturated, and several studies 13 , 19 , 21 , 24 have suggested that the under-saturated N 2 O in the NC surface water may be related to the dilution of melting sea ice.…”
Section: Resultsmentioning
confidence: 99%
“…The positive N 2 O fluxes were estimated by Hirota et al 20 , although their research area was limited to the south of the SC, and the investigation was conducted in few locations. Wu et al 21 and Zhan et al 23 likewise estimated positive N 2 O fluxes in the SC and negative N 2 O fluxes in the NC, although the flux values were calculated using only one model. In addition, Fenwick et al 19 estimated relatively lower fluxes, suggesting that these results may be due to either of the different calculation approaches (e.g., weighted mean wind data over 60 days prior to sampling), varying oceanographic conditions (e.g., dilution by melting of sea ice with low N 2 O concentration) or both.…”
Section: Resultsmentioning
confidence: 99%